MRI OPPORTUNITIES IN CERVICAL CANCER LOCAL STAGING PREOPERATIVE EVALUATION - N. A. Rubtsova; E. G. Novikova; V. E. Sinitsyn (Акушерство, гинекология и репродукция)
Objective: The purpose of this study is to elucidate the opportunities of magnetic resonance imaging (MRI) for local staging perioperative evaluation in patients with cervical cancer.Materials and methods: 253 253 patients with cervical cancer were included in study. All patients underwent examination and treatment in the Herzen Moscow Research Cancer Institute. Average age of patients was 35 + 5.6 years (21-67 years). Patients were divided int two groups: I-group included 114 woman, in which patients underwent surgical treatment and 56 patients on chemoradiation therapy, that preceded the surgery; II-group included 83 patients, in which the first stage of treatment was neoadjuvant therapy. MRI was performed in all patients within one week before radical surgery. MRI results have been compared with the histopathological report of the hysterectomy specimen. Results: The accuracy, sensitivity and specificity of MRI for perioperative evaluationof cervical cancer local staging in I group were 87%, 67%, 81%, positive predictive values (PPVs) and negative predictive values (NPVs) were 94% and 56%, respectively. For II group accuracy, sensitivity and specificity of MRI were 72%, 90%, 83%, PPVs and NPVs were 83%. Conclusion: MRI has a high diagnostic performance in preoperative staging of cervical cancer, content regardless of neoadjuvantt herapy. MRI allows to optimize the individual treatment plan in patients with cervical cancer.